2022
DOI: 10.1155/2022/9565136
|View full text |Cite|
|
Sign up to set email alerts
|

Antidiabetic Effect of Tamarindus indica and Momordica charantia and Downregulation of TET-1 Gene Expression by Saroglitazar in Glucose Feed Adipocytes and Their Involvement in the Type 2 Diabetes-Associated Inflammation In Vitro

Abstract: To date, there is no satisfactory and effective therapy available to cure type 2 diabetes mellitus (T2DM). This present work is focused on plant extracts and the effect of saroglitazar and TET genes on oxidative stress and inflammation in vitro adipocytes. Aqueous extracts of Tamarindus indica and Momordica charantia seed have shown potent antidiabetic activity that decreases glucose levels in diabetic adipocytes. After seven and fourteen days, the sugar level in the blood was significantly reduced when plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Our previous work has proven the effectiveness of these two plants in the treatment of diabetes [ 6 ]. Other authors have also proven the use and therapeutic virtues of these two plants [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work has proven the effectiveness of these two plants in the treatment of diabetes [ 6 ]. Other authors have also proven the use and therapeutic virtues of these two plants [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%